Analysis of Pine Forest-Based Ecotourism Management Strategies to Support Landscape Sustainability in Purworejo Regency, Indonesia - Nike Triwahyuningsih; Dhani Suryawan (Green Engineering Society, 2026)
Pine forest-based ecotourism has significant potential to support sustainable landscape management and rural development. This study aims to formulate strategic management directions for pine forest-based ecotourism in Kalilo Pine Forest, Purworejo Regency, using an integrated SWOT-based landscape sustainability approach. The research employed a descriptive, qualitative, and quantitative case study design involving 30 respondents, including tourism managers, local community members, and village officials. Data were collected through field observations, interviews, and questionnaires using a Likert scale (1-4). Data analysis was conducted using Internal Factor Analysis Summary (IFAS) and External Factor Analysis Summary (EFAS), followed by a SWOT matrix and strategy prioritization. The results indicate that Kalilo Pine Forest achieved an IFAS score of 2.70 and an EFAS score of 2.82, placing it in Quadrant I, which indicates strong internal capacity and favorable external opportunities. Priority strategies include the development of conservation-based educational ecotourism programs, strengthening community management capacity, and implementing environmental carrying capacity controls. This study contributes to sustainable tourism planning by integrating SWOT strategic analysis with ecological, social, and economic landscape sustainability considerations. The findings provide practical policy directions for improving ecotourism governance through the development of standard operating procedures and visitor management systems to support long-term sustainability.